Evaluation of Viscoelastic Adhesion Strength and Stability of Composite Waterproofing Sheet Using Non-Hardening Viscoelastic Synthetic Polymer-Based Rubber Gel - Junhong Jeon; Kyuhwan Oh; Sooyeon Kim; Bo Jiang; Xingyang He; Sangkeun Oh (Applied Sciences, 2022)
Recently, a non-hardening type synthetic polymerized rubber gel (hereinafter referred to as NHV-SPRG) composite waterproofing sheet has been used on construction site as a new waterproofing technology. In this study, a test method is proposed in which a composite waterproof sheet is attached to an area of 150 mm in length and 100 mm in width on the mortar-based substrate specimen, and subsequently peeled off at 180 ° vertically to measure the “peel load (N)” at 10 points of 10 mm intervals (P1~P10, from 30 mm point to 120 mm point). Value obtained by dividing the average value of the measured peeling load by a width of 100 mm was defined as “viscoelastic adhesion strength (N/mm)”. The viscoelastic adhesive strength evaluated for the NHV-SPRG composite waterproof sheet of 4 types (VG-1, VG-2, VG-3, VG-4) was an average of 1.99 N/mm. To examine the effectiveness of the viscoelastic adhesive strength, the adhesion stability was evaluated based on the peel load’s coefficient of variation, grade of the linear regression line of the peel load, and peel load percent relative range in peel load for each section of the composite waterproofing layer. As a result, the VG-2 type was measured to have the highest viscoelastic adhesive strength, but the VG-1 type was confirmed to have the highest adhesive stability. Considering these results, it is judged that even a product with high adhesion can have varying stability in terms of performance that can affect construction precision. The test method and performance standard value for the viscoelastic adhesion strength proposed as an evaluation index through this study are expected to be used as a quality control standard to secure the on-site adhesion stability of the NHV-SPRG composite waterproof sheet.